1982
DOI: 10.4319/lo.1982.27.6.1029
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment by bottom currents in Lake Erie

Abstract: Previous studies of the central basin of Lake Erie have indicated, on the basis of lakewide budgets of heat and dissolved oxygen, that the thickness of the hypolimnion and the interaction of the hypolimnion with the overlying fluicl are important factors governing the dissolved oxygen concentration in the near-bottom water. Data collcctcd during an intensive field program in 1979 contain an example of an event during which both the thickness and temperature of the hypolimnion incrcasc due to an erosion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…where ub is the daily average scalar speed from a current meter at the site (3.3 m off the bottom) and C,= 1 x 10-3-a value which compares favorably with the estimates in Ivey and Boyce (1982) and the suggested values of Sternberg (1972). Typical values of (&)b are then of the order of 0.2 cm.…”
Section: The Numerical Modelsupporting
confidence: 68%
See 3 more Smart Citations
“…where ub is the daily average scalar speed from a current meter at the site (3.3 m off the bottom) and C,= 1 x 10-3-a value which compares favorably with the estimates in Ivey and Boyce (1982) and the suggested values of Sternberg (1972). Typical values of (&)b are then of the order of 0.2 cm.…”
Section: The Numerical Modelsupporting
confidence: 68%
“…We chose to simulate the month from mid-July to mid-August during the field year 1979 for several reasons: the lake was strongly stratified during that period, while at the same time there were storm events which drove strong mixing events in the UML; Ivey and Boyce (1982) had shown that changes in the BML properties were predominantly due to vertical mixing; the timespan encompassed a period where the largest increases in BML thickness were observed over the summer period; and the late summer is important as the bottom water may become anoxic at this time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous publications address the limitations of (Stauffer 1985(Stauffer , 1993 and justifications for (Patterson et al 1984) this assumption. A number of recent studies, however, show spatial heterogeneity in turbulent events (EtemadShahidi and Imberger 2001, Saggio and Imberger 2001, MacIntyre et al 2002, Boegman et al 2003, MacIntyre et al 2006, Na and Park 2006; and yet others connect dynamic physical processes to spatial heterogeneity in biological and chemical variables (Ivey and Boyce 1982, Stauffer 1985, MacIntyre and Melack 1995, MacIntyre and Jellison 2001, Eckert et al 2002, Chao et al 2006, Marce et al 2007). …”
Section: Introductionmentioning
confidence: 99%